Sustainable Lessons Learnt from the Attitudes of Language Instructors toward Computer-Assisted Language Teaching - Adedokun, Theophilus Adedayo; Zulu, Sylvia Phiwani; Awung, Felix Nkwatta; Usadolo, Sam Erevbenagie (Research in Social Sciences and Technology, 2023)
Technology has significantly influenced the educational field, including language teaching. However, some language instructors hold negative attitudes toward technology, particularly computer-assisted language teaching (CALT), which may affect the advancement of language teaching. This study examines the attitudes of language instructors toward CALT in some South African public universities and identifies sustainable lessons that could promote the use of CALT. The study employed a quantitative research approach using content analysis and surveys to comprehensively investigate language instructors’ attitudes toward CALT. Surveys provided the required information about the attitudes of language instructors toward CALT, and content analysis and descriptive statistics were used to analyze the data and identify sustainable lessons from the attitudes of the language instructors toward CALT. Descriptive statistics were used to summarize the survey results. The analysis revealed that some language instructors have negative attitudes toward CALT, suggesting that institutions require a fundamental approach to advance the use of CALT. Sustainable lessons learned from the attitudes of language instructors toward CALT are identified, and recommendations are made about how to implement effective CALT on a personal and institutional basis. This study highlights the importance of a positive attitude toward CALT and developing a fundamental approach to using CALT in language teaching. The sustainable lessons learned from this study could inform and advance language teaching practices that employ CALT, inform future research, and promote effective language teaching practices that use CALT.